Efficient degradation of methyl orange through photo-Fenton processes with MIL-100(Fe) modified Fe\(_3\)O\(_4\) (Fe\(_3\)O\(_4\)@MIL-100(Fe)) catalyst - Puspitasari, Melani Puji; Pratama, Jeesica Hermayanti; Nugroho, Roshid Adi; Lestari, Witri Wahyu; Kemala, Yusnadia; Saraswati, Teguh Endah; Fansuri, Hamzah; Mukti, Rino Rakhmata; Suharbiansah, Rujito S. R. (Communications in Science and Technology, 2024)
The research successfully synthesized a composite MIL-100(Fe) modified Fe3O4 (Fe3O4@MIL-100(Fe)) catalyst and examined its efficiency in degrading methyl orange (MO) through the photo-Fenton process compared to Fenton. The different percentages of Fe3O4 were integrated into MIL-100(Fe) and their effects on material characteristics and degradation capabilities were studied. Ex-situ synthesis involved varying Fe3O4 weight ratios (3, 10, and 20% w/w). Characterization techniques confirmed the integration of Fe3O4 and MIL-100(Fe) and revealed changes in surface area, pore size, and thermal stability with Fe3O4 addition. Meanwhile, removal tests showed promising results with the photo-Fenton process exhibiting maximum efficiency (95.51%) using 10% Fe3O4@MIL-100(Fe). This study provides valuable insights into developing efficient photo-Fenton catalysts for environmental remediation, particularly for addressing dye pollution in wastewater by highlighting the potential of Fe3O4@MIL-100(Fe) composites in this context.